2016
DOI: 10.1111/jam.13352
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of recombinantLactobacillus casei-expressing F4 (K88) fimbrial adhesin FaeG in conjunction with a heat-labile enterotoxin A (LTAK63) and heat-labile enterotoxin B (LTB) of enterotoxigenicEscherichia colias an oral adjuvant in mice

Abstract: Recombinant Lactobacillus provides a promising platform for the development of vaccines against F4+ ETEC infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…[80]. However, several current studies have point out that immunostimulatory function showed tissue-specific differences among DCs in terms of inducing T helper (Th) cell responses [35, [130][131][132] and recommended that Lactobacillus species are actively concerned in the improvement of adaptive immune responses by programming many aspects of CD4+ T cell differentiation [80]. In additional many Lactobacillus species are microbe-associated molecular pattern (MAMPs) is capable of interacting with epithelial pattern recognition receptors, mainly the Toll-like receptor-2 (TLR2), TLR6 and nod-like receptors which leads to an up-regulation of signaling pathways to modulate the host's immune response [139,140].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[80]. However, several current studies have point out that immunostimulatory function showed tissue-specific differences among DCs in terms of inducing T helper (Th) cell responses [35, [130][131][132] and recommended that Lactobacillus species are actively concerned in the improvement of adaptive immune responses by programming many aspects of CD4+ T cell differentiation [80]. In additional many Lactobacillus species are microbe-associated molecular pattern (MAMPs) is capable of interacting with epithelial pattern recognition receptors, mainly the Toll-like receptor-2 (TLR2), TLR6 and nod-like receptors which leads to an up-regulation of signaling pathways to modulate the host's immune response [139,140].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus species are known to influence the immune response in a strain-dependent manner; therefore, they are good candidates for developing innovative oral vectors, comprising good options to reduce the strength of pathogens, meant for mucosal delivery approaches [124,130]. Lately, ever-increasing confirmation supported that Lactobacillus strains expression systems, through expression and delivery of antigens/adjuvant, are hopeful oral vaccine vectors, due to their: efficient delivery of immunogens to the mucosal inductive locations, exceptional safety, reduced antigen degradation and prevention of protein purification On the use of Lactobacillus species as mucosal delivery vectors for therapeutic proteins and DNA vaccines such as expression signals and host strains, for the heterologous expression of therapeutic proteins such as antigens, cytokines and enzymes [133,134].…”
Section: Lactobacillus Species As Mucosal Delivery Vectors For Dna Vamentioning
confidence: 99%
See 2 more Smart Citations
“…A study compared expression efficacy of rLTB in Pichia pastoris with that in E. coli , demonstrating that a higher expression level and adjuvant activity of rLTB could be obtained by using P. pastoris as the expression host [6]. Another study proved that LTB expressed in fusion with antigens in engineered Lactobacillus can significantly enhance the local and systemic immune responses to the antigens [10, 11]. Recently, increasing evidences supported that food-grade L. lactis expression systems, through expression and delivery of antigens/adjuvants, are promising oral vaccine vectors, particularly owing to their outstanding safety, avoidance of protein purification, reduced antigen degradation and efficient delivery of immunogens to the mucosal inductive sites [12, 13].…”
Section: Introductionmentioning
confidence: 99%